Pengaruh Promosi, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Titipan Kilat JNE Medan - Bagus Handoko (Universitas Muhammadiyah Sumatera Utara, 2017)
The purpose of this study is to determine whether there is influence Promotion, Price and Quality Service to Customer Satisfaction at PT. Maxim Housewares Indonesia Medan. The result of this research is there is significant influence of Promotion to Consumer Satisfaction, The amount of influence of Promotion on Consumer Satisfaction is 20,9% There is significant influence of Price to Customer Satisfaction, the amount of influence Price to Customer Satisfaction is equal to 16,2% There is significant influence Quality service to consumer satisfaction, the amount of influence Quality of service to Customer Satisfaction is equal to 63.6% Promotion, Price and Quality of service together significant effect on Consumer Satisfaction at PT. Maxim Houseware Indonesia Medan, with the capability of Promotion, Price, and Quality of service to explain customer satisfaction is equal to 82,5% while the rest equal to 17,5% explained by another variable not included in this research model.